University Education of Pedagogues Meeting Demands of School Practice - Anđelković, Aleksandra K.; Popović, Daliborka R. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
University education is met with new demands for different models of work which will more successfully prepare students for societal challenges, a higher quality of involvement in school practice, and a constant personal adaptability. The duty of university education is to meet the needs of society by constantly raising the level and quality of its curricula and thus influence the quality of candidate preparation which is needed for the work environment. However, the quality of education of future candidates should be monitored through the school practice; therefore, university teaching models need to rely on strengths and weakness observed in practice as well as on legislative guidelines which regulate the work of school pedagogues. The goal of this research is focused on the examination of attitudes of pedagogy specalists and pedagogy students, as well as on differences in opinion on the influence of initial education on the application of theoretical knowledge and the development of skills which are related to concrete tasks in school practice. The obtained results showed that there are statistically significant differences between opinions of students and pedagogues when it comes to certain items: participating in and making institution’s annual work plan; preparing yearly and monthly pedagogue work plans; forming classes; monitoring of educational work; providing support for teachers in working with students who need additional support.